Paul's use of 'Christ Rhetoric' in 1 Corinthians: a case study from 1 Corinthians 15:1-34 - Mascrenghe, Mark Alroy (Department of Religious Studies, 2022)
While many scholars have used classical rhetoric for the interpretation of 1 Corinthians, others have proposed alternate methods for the same purpose. The problem with these methods is that they are not based on a closer reading of Paul, rather they are based on different flavors of the rhetorical system and sociological theories. My own approach to this problem is to look at the text of 1 Corinthians with an eye for methodology. A careful analysis of the 1 Corinthian passages yields Paul's rhetorical methods that are different to the classical rhetoric and modern scholars' attempts to find new rhetorical methods. The rhetoric in 1 Corinthians is unique because in every significant issue Paul addresses, he uses a Christ centered response. As such, it calls for a recognition of a Christ centered rhetoric, thus the name Christ Rhetoric. This rhetoric is used often enough in 1 Corinthians to be formalized into a rhetorical/interpretive methodology with its own structure, topoi, and argumentative methods. This resultant methodology is then applied to 1 Corinthians 15:1-34 as a case study.